Pengaruh brand image dan celebrity endorser terhadap minat beli produk skincare Ms Glow - Tambunan, Sayyidatul Aulia; Parhusip, Austin Alexander (ARKA INSTITUTE, 2023)
This study aims to determine the effect of brand image and celebrity endorser on purchasing interest in MS Glow skincare products among students of the Management Study Program, Faculty of Economics and Business, Potensi Utama University. This type of research is quantitative using descriptive statistical methods and using the Slovin method sampling technique. The data used in this study are primary data with a sample size of 225 respondents of students of the Management Study Program, Potensi Utama University. The analysis technique used is multiple linear regression analysis. Based on the results of the study, it simultaneously shows that the brand image and celebrity endorser variables have a significant and positive effect on consumer purchasing interest. And through the test results, it can be seen that the Adjusted R determination coefficient value shows that the purchase interest variable can be explained by the brand image and celebrity endorser variables while the rest can be explained by other factors not discussed in this study. It can be concluded that the better the brand image and celebrity endorser, the greater the purchase interest obtained in MS Glow products.